Revivalism and Exegetical Reception of At-Tahm in Islamic Higher Education - Wahidah, Fatira; Ikhsan, Muh.; Halid, Yusrifah; Amir, Abdul Muiz (Islam Realitas: Journal of Islamic and Social Studies, 2022)
This research aims to determine whether or not revivalism ideology exists among academics in Islamic higher education institutes in the province of Southeast Sulawesi. It is accomplished through the use of an exegetical reception approach of their understanding of the AÌ„yÄt at-TahÌ£kÄ«m (Quran chapter al-Midah [5]:44-47). Data was gathered by combining survey technique development with in-depth interviews. The collected data was analyzed using a philosophical and phenomenological hermeneutic approach to assess the academic communitys understanding of AÌ„yÄt at-TahÌ£kÄ«m. According to the survey results, AÌ„yÄt at-TahÌ£kÄ«m is very popular among academics higher education institutes in Southeast Sulawesi. Most of the academic communityâ€™s information comes from religious studies on social media. They acknowledge and accept these verses as the foundation for the legitimacy of kaffah enforcement of Islamic law as the foundation for Indonesiaâ€™s political system. Meanwhile, the interviews show that most informants label those who disagree with the discourse with theological labels (kÄfir and thÄgÅ«t). As a result, even though these characteristics have not reached an extreme level, their comprehension is included in the revivalism ideologys characteristics. Penelitian ini bertujuan untuk menakar eksistensi karakteristik ideologi revivalisme di kalangan sivitas akademika, khususnya di perguruan tinggi yang berada di wilayah provinsi Sulawesi Tenggara, Indonesia. Ini dilakukan dengan menerapkan pendekatan resepsi eksegesis atas pemahaman mereka terhadap AÌ„yÄt at-TahÌ£kÄ«m (Q. al-Midah [5]:44-47). Data penelitian ini dikumpulkan melalui elaborasi antara teknik survey dan wawancara mendalam secara bersamaan. Data yang diperoleh kemudian dianalisis mengggunakan pendekatan hermeneutika filosofis dan fenomenologis guna menakar pemahaman sivitas akademika terhadap AÌ„yÄt at-TahÌ£kÄ«m. Hasil survey membuktikan bahwa AÌ„yÄt at-TahÌ£kÄ«m cukup populer bagi kalangan sivitas akademika di Sulawesi Tenggara. Informasi tentangnya mayoritas diakses oleh sivitas akademika dari kajian-kajian keagamaan di media sosial. Mereka mengenal dan memahami ayat-ayat itu sebagai basis legitimasi wajibnya penegakan syariat Islam secara kaffah sebagai basis sistem politik pemerintahan di Indonesia. Sedangkan hasil wawancara membuktikan bahwa mayoritas informan menggunakan label-label teologis (kafir dan thagt) terhadap orang-orang yang menolak wacana tersebut. Meskipun pemahaman mereka dapat dikategorikan mengandung karakteristik ideologi revivalisme, tetapi belum termasuk level yang ekstrem, sehingga masih berpeluang bagi mereka untuk mendapatkan pembinaan.